Anatomic sites of disease in colorectal cancer patients recorded at the time of cytoreductive surgery for peritoneal metastases. Issue 5 (May 2022) - Sugarbaker, Paul H.; Chang, David
Abstract: Background: Peritoneal metastases is the second most common colorectal cancer dissemination. The anatomic sites at which colorectal peritoneal metastases are located within the abdomen and pelvis has not been previously determined. Methods: A prospective database has been maintained on patients treated by cytoreductive surgery (CRS) plus perioperative chemotherapy. The patients in this current study all had peritoneal metastases histologically confirmed, and a complete cytoreduction. The patterns of dissemination of the peritoneal metastases recorded after a prior left colon resection or right colon resection at the time of the CRS were analyzed. The major goal was to identify the location of colorectal cancer peritoneal metastases at abdominopelvic anatomic sites. Results: In these 77 patients, by the abdominopelvic regions, the highest incidence of histologically documented cancer was the pelvis (85.7%), central region (75.3%), right upper quadrant (50.6%) and right lower (53.2%). Specific anatomic sites free of disease at the time of primary resection at which cancer was documented at the time of CRS was the abdominal incision or laparoscopy port sites at 57.1% and the anatomic site for the primary cancer resection at 76.6%. Right colon cancer had a statistically significant increase in the right flank region 8 (p = 0.0350) and borderline significant increase of left colon cancer in the left lower region 5 (p = 0.0699). Conclusions: When data is pooled from many patients, physiology of the peritoneal spaces and tumor cell entrapment contribute to the distribution of disease within the abdomen and pelvis.